Determining the effectiveness of risk process practice in Malaysia's urban landscape planning project lifecycle - S. Muthuveeran, Adam Aruldewan; Mokhtar Azizi, Zahirah; Mustaffa Kamal, Mohd Firdaus; Yin, Izuandi; Wenyi, Chen (Leeds Beckett University, 2024)
Many urban landscape planning project risks become issues if not handled early. Risk management is necessary to control these undesirable risks through a project lifecycle risk process. Risk management is a well-established topic with global applications. However, research on integrating the risk process into the project lifecycle is uncommon. This study aims to examine how well the present risk process practice works throughout the project lifecycle. The aim of the study was achieved by conducting a thorough analysis of the risk process practice in the urban landscape planning project lifecycle. Within the project lifecycle phase, the practice effectiveness examined characteristics of risk process planning, process sequentialness, and completeness of each process stage. An investigative case study was used in the research technique. An expert interview with twelve landscape practitioners overseeing urban landscape planning projects in Malaysia was used to gather data. The content analysis approach is then applied to analyse it to create a topic and categorise, describe, and synthesise a thematic map. According to the study, the risk process is insufficiently integrated into the landscape architecture project lifecycle. The process is applied ad hoc and unplanned as risk process practice, beginning in the middle of the project lifecycle phase. Secondly, the risk process is applied intermittently since the risk is applied randomly and nonsequentially over the project lifecycle stage. Third, risk process techniques are incomplete because they only cover process steps. The practice restricted project performance risk management benefits. Infective integration causes project risk to be realised late in the lifecycle, managed poorly, and executed informally. The urban landscape risk management process should be elevated in urban landscape planning practice by integrating it into the project lifecycle framework.